New evidence supports RYR3 as a candidate gene for developmental and epileptic encephalopathy - Li, Jieling; Ou, Yuexu; Duan, Yuanhui; Gan, Xiaoming; Liu, Hu; Cao, Jie (Frontiers in Neurology, 2024)
Background: The ryanodine receptor 3 (RYR3) is involved in skeletal muscle contraction by releasing calcium from the sarcoplasmic reticulum and subsequent T-tubule depolarization. It is also expressed in the brain, and variants in the RYR3 gene can lead to congenital myopathy type 20 (MIM: #620310).Methods: We retrospectively analyzed the clinical characteristics and prognosis of a case of West syndrome, developmental and epileptic encephalopathy (DEE) caused by a missense variant in the RYR3 gene. We also reviewed and summarized the literature on epilepsy cases caused by RYR3 gene variants.Results: A 10-month-old female child with delayed psychomotor development and recurrent spasm-like seizures was diagnosed with infantile spasm syndrome and DEE. Treatment with various antiepileptic drugs resulted in initial improvement but ultimately failed to control the seizures. Whole-exome sequencing revealed a novel heterozygous variant c.10943C>T/p.T3648M in the RYR3 gene, and genome-wide sequencing ruled out other potentially pathogenic variants. Three previous reports have described RYR3 variants causing DEE, two of which were attributed to de novo heterozygous variants, and one was a compound heterozygote.The present case of DEE caused by a RYR3 heterozygous variant is consistent with previous rare cases of epilepsy caused by RYR3 gene variants in terms of pathogenesis and clinical features, but significantly different from congenital myopathy type 20. Our findings provide important evidence for the diagnosis of RYR3-related DEE, and we hypothesize that RYR3 gain-of-function variants resulting in "leaky" Ca2+ release channels may be a molecular genetic feature leading to DEE rather than myopathy.